Filme bioativo de amido de mandioca com extrato de Physalis peruviana - Mikolaiczik, Bianca Helena Kufner (2020)
Plant extracts have been studied in order to develop methods of biocontrol of fungi and bacteria, and the secondary metabolites extracted from these plant materials are mainly responsible for antifungal activity. The Physalis peruviana Linnaeus fruit is considered a natural functional food due to the presence of bioactive compounds, such as phenolic acids, flavonoids, and because of its antioxidant capacity. The use of bioactive compounds extracted from plants can promote health effects, as well as increase the shelf life of foods, since many of these compounds also act as antimicrobials and antifungals. In this way, they can replace synthetic antifungals and also incorporated in active packaging. Active packaging has the ability to interact with food, slowing degradation and extending its shelf life. In this way, the objective was to elaborate and characterize films of cassava starch incorporated from Physalis peruviana extract in different concentrations (control, 5%, 10%, 15% and 20%). The production of Physalis extract was carried out in an ultrasound bath for 2 hours, with a hydroalcoholic solution (50% water: 60% ethanol), soon after, the ethanol was evaporated in a rotary evaporator. Antifungal tests using the extract of Physalis were carried out and the extract's antifungal activity was verified against the Botrytis cinerea, from a concentration of 10% of extract. The characterization of the films occurred by analyzing the content of phenolic compounds, antioxidant activity (FRAP and DPPH), thickness, color and opacity, water vapor permeability, solubility, mechanical properties (tensile strength, elongation percentage and modulus Young), morphological properties (SEM), Fourier transformed infrared spectroscopy (FTIR-ATR) and thermogravimetry. It was found that the addition of extract decreased the water vapor permeability and solubility. The films showed a reduction in tensile strength and an increase in the elongation percentage, determining that the extract promoted a plasticizing effect on the films. Thermogravimetric analysis proved the interaction of the extract components with the starch film material, changing the degradation temperature of the compounds. The antifungal activity of the extract of Physalis peruviana against the fungus Botrytis cinerea was verified and positive characteristics were observed for the elaboration of active biodegradable films with the application of the extract of Physalis peruviana, such as homogeneity and malleability.